Wakaf uang sebagai instrumen pemulihan ekonomi nasional: Tinjauan literatur komprehensif mengenai potensi, regulasi, dan implementasi di Indonesia - maghfiroh, ulfa fira (Maliki Interdisciplinary Journal, 2026)
This study analyzes the strategic role of money waqf as an alternative financing instrument in the framework of the National Economic Recovery after the crisis due to the COVID-19 pandemic and the threat of global recession. In the midst of limited government fiscal space, money waqf offers financing schemes based on social participation and economic justice. With the largest Muslim population in the world, the potential for money waqf in Indonesia is estimated to reach Rp180 trillion per year, but the realization of its collection is still far below this potential. This study examines the regulatory framework starting from Law No. 41/2004, Government Regulation No. 42/2006, to the 2002 MUI fatwa as well as innovations in social financial instruments such as Cash Waqf Linked Sukuk (CWLS) and Cash Waqf Linked Deposit (CWLD). Through a literature review of data from the Indonesian Waqf Agency (BWI), the Ministry of Finance, and academic references, this study identified the main obstacles in the form of low waqf literacy, institutional problems, and low public trust in nazhir professionalism. The findings confirm that the integration of money waqf in the formal financial system, if managed with transparent digital governance, has the potential to become an automatic economic stabilizer, a driver of MSME empowerment, and a catalyst for equitable distribution of welfare.